738 Lessons from the National Patient Safety Agency Alerts. (12th October 2021) - Lee, Rachel; Hatt, Jacob; Mahawar, Kamal; Bansal, Mohit; Goyal, Amit; Madhok, Brijesh
Abstract: Aim: The National Patient Safety Agency (NPSA) reviews incident reports from all NHS trusts, and reports deemed critical are issued as NPSA alerts. We aim to highlight important learning points from NPSA alerts to facilitate wider dissemination and prevent similar incidents, and overall improve patient safety. Method: All patient safety alerts obtained from NPSA since inception (2008) till June 2020 were screened. We identified safety alerts that could be relevant to surgical practice, and further details of each alert were obtained from the Central Alerting System (CAS) website. Information obtained from CAS website was reviewed by consultant surgeons to identify specific learning points. Results: 1857 alerts were reported by NPSA of which 94 were relevant to surgical practice. Alerts were grouped into four themes: pre-operative(N = 4), intra-operative(N = 34), post-operative(N = 29), others(N = 8), and no specific learning point identified(N = 19). Pre-operative alerts focused on safety checks to avoid errors and improve patient safety e.g., WHO checklist. Majority of the intra-operative alerts were due to difficulty with use of specific equipment(n = 22) e.g., advanced haemostatic devices. Post-operative alerts highlighted specific issues with implants especially in breast and orthopaedic surgery(N = 23), and patient review following procedures(N = 6). Conclusions: In spite of alerts occurring in a specific speciality, there is wider applicability to all surgical specialities e.g., pre-operative risk assessment in elderly patients requiring urgent surgery or confirming pregnancy status in immediate pre-operative period. Emphasis should be laid on staff training on using specialist equipment including troubleshooting. Raising awareness of these NPSA alerts may help prevent similar incidents.